Studi Komparatif Penggunaan Platform Zoom dan Google Classroom sebagai Media Perkuliahan Daring - Intan Cynara Valentina Putri; Rahmi Mudia Alti; Yoana Nurul Asri; Ike Yuni Wulandari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
In this study, a comparative study was conducted on the use of the Google Classroom and Zoom Meeting platforms during online lectures held at Nurtanio University. The object of research is students from various study programs at Nurtanio University, totaling 82 people. Data were obtained from questionnaires filled out by students on a google form with an ordinal scale. The questionnaire is divided into three components (lecture implementation, lecturer capabilities, and facilities and infrastructure) with a total of 15 statement items that compare perceptions of using Google Classroom and Zoom platforms. Overall, students gave a perception of the "good" category on the three assessment components with an average score for the Zoom and Google classroom platforms respectively 4.07 and 3.90 in the implementation of lectures, an average score of 4.06 and 3.96 for lecturer capabilities, and an average score an average of 3.84 and 3.76 for facilities and infrastructure. To find out whether there is a difference in student perceptions on the two platforms, a statistical test using SPSS is carried out, namely the Wilcoxon marked rank test. The results obtained are that there are differences in student perceptions on the use of the two lecture platforms, namely the perception of students using Google Classroom is better than using Zoom as evidenced by the Asymp score. Sig. (2-tailed) = 0.007 and Z value = 2.692.